(untitled) (Revista da Tulha, 2021)
Experience report about the maintenance of the activities bound to the Engenho Musical extension program (Music Department and Pro Rectory of Extension from Udesc/Ceart) during the period of social isolation/distancing and the consequent suspension of in-person collective activities due to the Covid-19 pandemic, referring to the period between March 2020 to August 2021. The utilized methodology contemplated a bibliographic survey of academic articles and works about the subjects referring to the Covid-19 pandemic and musical groups, followed by a critical discussion about the collective musical activity experiences during the mentioned period and the application of a quantitative-qualitative research(questionnaire with objective questions and open-ended questions directed to the integrants of the referred program that maintained activity during the pandemic). The collected works allowed a discussion of the impacts of the pandemic on the collective musical practices and the necessary adaptations to the maintenance of the activities, enabling a confluence with the actions adopted in the Engenho Musical extension program and its integrants reports.